The Institutions of Monetary Policy - King, Mervyn (American Economic Review, 2004)
To have one central bank governor address you today may be regarded as a misfortune, but to invite two looks like carelessness! It is a great honour to be invited by this year’s President-Elect, Marty Feldstein, to deliver the Ely lecture. Marty has been my teacher, mentor, colleague and friend for over thirty years, and I never cease to be amazed by the energy and imagination which he devotes to the study of economic problems. I got to know Marty during my time as a Kennedy Scholar at Harvard in 1971. The Kennedy Scholarships form one part of Britain's national memorial to President Kennedy. The other part is an acre of land, now American territory, at Runnymede. At the ceremony to open the Runnymede memorial in 1965, Prime Minister Harold Wilson remarked about President Kennedy that "his eyes were on the horizon, but his feet were on the ground”. Almost thirty years earlier Richard T. Ely published his autobiography entitled "Ground under Our Feet". Whereas I found the experience of coming from Europe to the United States intellectually liberating and exhilarating, a hundred years earlier Ely found academic freedom by making the reverse journey. As